Clinical Importance of Diastolic Sonoelastographic Scoring in the Management of Thyroid Nodules - Yerli, H.; Yilmaz, T.; Oztop, I. (American Journal of Neuroradiology, 2013)
SUMMARY: We determined that the application of a 5-point scoring method by using an external manual compression method synchronized with the diastolic period of the carotid artery by sonoelastography was helpful in the management of thyroid nodules. The mean scores on sonoelastography were 2.74 ± 0.97 for 62 benign nodules and 3.90 ± 0.88 for 10 malignant nodules (P < .01). Eighty-seven percent of benign nodules were determined when a cutoff point between scores 3 and 4 was used. FNABfine-needle aspiration biopsySRUSociety of Radiologists in Ultrasound